Parables and fables as distinctive Jewish literary genres the origins and structure of indirect speech about God - Caspi, Mishael, 1932-; Greene, John T. (Lewiston, N.Y. : Edwin Mellen Press, 2011)
A book that concerns itself with the historical development of the fable or parable as a way of communicating knowledge and truth, in both Judaism and Christianity.
Includes bibliographical references and index.
Description based upon print version of record.
Keywords: Bible -- Parables; Narration in the Bible; God in literature; Jesus Christ -- Parables; Parables in rabbinical literature; Jewish parables; Jewish legends; Fables; Bible -- Criticism, interpretation, etc; Rabbinical literature -- History and criticism; Bible -- Criticism, interpretation, etc; Bible -- Parables; Fables; God in literature; Jesus Christ -- Parables; Jewish legends; Jewish parables; Narration in the Bible; Parables in rabbinical literature; Rabbinical literature -- History and criticism; Religion; RELIGION / Judaism / Sacred Writings; Electronic books